The Structural Level in the Poem “Africa Is Our Land” by Dāwūd ‘Abd al-Bāqī A Grammatical Semantic Study: Syntax-Semantics - Mukadam, Abdur -Rasheed Mahmoud-; Abdussalam, Muhyideen Ademola (Al-Ḍād Journal, 2022)
The structure is joining a vocabulary to another, and there are three types of Arabic vocabulary: Ism (Noun), Fi’l (Verb) and Ḥarf (Preposition), and among the different types of Arabic structures is predicate structure which forms the meaningful speech that is meant in this research. Nominal sentence consists of a noun and a noun while actual sentence consists of a verb and a noun and each of these two sentences has rules, patters, purposes, and meanings. This research will study the two sentences in Dr. Dāwūd ‘Abd al-Bāqī Muḥammad’s poem entitled (The Structural level in the Poem “Africa Is Our Land” by Dāwūd ‘Abd al-Bāqī – A Grammatical Semantic Study). The study aims to reveal what the poem was restricted to among the special structural rules and grammatical patters. This research consists of an introduction containing aims, objectives, problem, and plan of the study, and a preface containing the introduction of the poet and presentation of the poem, and two chapters; the first chapter is nominal sentence, and the second chapter is actual sentence, followed by a conclusion containing the most important results and recommendations. The researcher used descriptive analytical method in the study. Keywords: structural level, Africa, poem, grammatical semantic